2021
DOI: 10.1002/mar.21491
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing users' adoption and use of conversational agents: A systematic review

Abstract: As artificially intelligent conversational agents (ICAs) become a popular customer service solution for businesses, understanding the drivers of user acceptance of ICAs is critical to ensure its successful implementation. To provide a comprehensive review of factors affecting consumers' adoption and use of ICAs, this study performs a systematic literature review of extant empirical research on this topic. Based on a literature search performed in July 2019 followed by a snowballing approach, 18 relevant articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 56 publications
(143 reference statements)
6
59
1
Order By: Relevance
“…On the one hand, consumers find the technology useful and convenient (i.e., the chatbot technology “frees” them from restrictive business hours in obtaining customer service); on the other hand, they perceive the technology as restricting their autonomy (i.e., the chatbot “enslaves” them, asking them to divulge personal information to enable its technological efficiency). In response to this paradox, consumers cope with the situation by mobilizing the privacy calculus defense tactic: “they weigh the expected benefits from online transactions against the perceived risks” (Lutz et al, 2020, p. 1169). More specifically, they accept less control over their personal information against increased personalized service.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, consumers find the technology useful and convenient (i.e., the chatbot technology “frees” them from restrictive business hours in obtaining customer service); on the other hand, they perceive the technology as restricting their autonomy (i.e., the chatbot “enslaves” them, asking them to divulge personal information to enable its technological efficiency). In response to this paradox, consumers cope with the situation by mobilizing the privacy calculus defense tactic: “they weigh the expected benefits from online transactions against the perceived risks” (Lutz et al, 2020, p. 1169). More specifically, they accept less control over their personal information against increased personalized service.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…We assume that users concerned about privacy threats may experience a sense of unease when interacting with the chatbot (Ischen et al, 2020), particularly as privacy concerns and creepiness are strongly correlated (Inman & Nikolova, 2017). Additionally, creepiness is a concept that can be understood in the context of privacy cynicism (Lutz et al, 2020), and the “privacy paradox” (Hoffmann et al, 2016). As consumers develop a feeling of uncertainty (one aspect of creepiness) and powerlessness over the decision to control disclosure of their private information, they are led to use the chatbot despite their privacy concerns, possibly heightening perceptions that intelligent technologies appear to be creepy.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the rapid adoption of chatbots in various industries, there are limited empirical data regarding the factors influencing consumer response to chatbots. Ling et al ( 2021 ) review of the emerging conversational agent research in marketing has identified varied types of variables, from usage considerations (e.g., perceived usefulness, perceived enjoyment) to bot characteristics (e.g., anthropomorphism, empathy) and user traits (e.g., personal innovativeness), which can impact consumers' attitude and evaluation. Specific to the study focus of the emotional context of consumer–chatbot interaction, prior studies have primarily addressed the usage considerations of utilitarian/cognitive versus hedonic/arousal factors (Sivaramakrishnan et al, 2007 ; Zarouali et al, 2018 ) driving consumer attitude toward the bot.…”
Section: Introductionmentioning
confidence: 99%